ANALISIS PONDASI TANDON PEMBAGI AIR BERSIH DI DESA PUCANGANAK KABUPATEN TRENGGALEK - Herry Widhiarto; Fajar Astuti Hermawati; Valantino Ateng Pamolango (JPM17: Jurnal Pengabdian Masyarakat, 2016)
The foundation is part of the structure of building which serves as amedium that receives the load of the building then pass those loads into theground. The material foundation must be able to withstand the work load andthe ground should be able to accept the burden passed on by the foundation.Ability of soil to receive the load depends on soil conditions, load received, thetype and dimensions of the foundation. The foundation itself is divided into twomajor groups, namely the foundation of shallow and deep foundations. The useof shallow foundation is considered if the soil layer is relatively good andrelatively light load on the structure. For poor soil conditions and load largestructures, deep foundations in more considered. Based on the existing soilconditions, the foundation plate square shape can support a load of clean waterreservoir and the consolidation settlement is relatively small.Keywords: shallow foundation, reservoir / reservoir, consolidation settlement